Syndemics and the biosocial conception of health. Issue 10072 (4th March 2017) - Singer, Merrill; Bulled, Nicola; Ostrach, Bayla; Mendenhall, Emily
Summary: The syndemics model of health focuses on the biosocial complex, which consists of interacting, co-present, or sequential diseases and the social and environmental factors that promote and enhance the negative effects of disease interaction. This emergent approach to health conception and clinical practice reconfigures conventional historical understanding of diseases as distinct entities in nature, separate from other diseases and independent of the social contexts in which they are found. Rather, all of these factors tend to interact synergistically in various and consequential ways, having a substantial impact on the health of individuals and whole populations. Specifically, a syndemics approach examines why certain diseases cluster (ie, multiple diseases affecting individuals and groups); the pathways through which they interact biologically in individuals and within populations, and thereby multiply their overall disease burden, and the ways in which social environments, especially conditions of social inequality and injustice, contribute to disease clustering and interaction as well as to vulnerability. In this Series, the contributions of the syndemics approach for understanding both interacting chronic diseases in social context, and the implications of a syndemics orientation to the issue of health rights, are examined.